European-Andalusian Communication and Its Impact on the European Renaissance: The Caliphate and Taifa Eras - khelfat, meftah (Journal of Social Sciences and Humanities, 2016)
The Arab-Islamic civilization in Al-Andalus served as a model for civilizational progress during the Middle Ages, not only through its scientific brilliance but also through its contributions to transforming Europe, which had long suffered from ignorance and ecclesiastical tyranny. At the same time, it reflected a unique experience of cultural fusion within Andalusian society, providing direct evidence of the religious tolerance that characterized Arab-Islamic rule in this part of the European continent; thus, it is considered one of the most successful human experiences in achieving societal aspirations. Undoubtedly, despite the turbulent political life in Al-Andalus caused by internal strife and repeated Christian campaigns from the north, these challenges did not directly hinder intellectual life or its steady growth. Al-Andalus maintained its scientific stature even under the darkest political conditions, becoming a destination for students from all over, especially Europe. This credit is largely due to the patronage of the princes and caliphs of Al-Andalus, who were deeply committed to spreading knowledge and showed great interest in supporting scholars and men of letters.